KEUNTUNGAN USAHA PENGOLAHAN LEMPOK DI KECAMATAN TEBING TINGGI KABUPATEN EMPAT LAWANG - Suryati, Nila (Jurnal AGRIBIS, 2021)
Durian (Durio zibethinus Murray) is one of tropical fruit in Indonesia. Durian can be processed to be any kind of food, such as Lempok. Lempok in Tebing Tinggi District Empat Lawang Residence was managed in household scale to small industry. Â The purpose of this research was to analyze production cost and benefit of lempok durian industry at Tebing Tinggi District Empat Lawang Residence. Research methode used on this research was case study, with respondence choosen purposively. From this research found that average production cost of this lempok industri as much as Rp. 151.255.732-, consist of average fixed cost Rp. 1.133.951 and average variable cost Rp. 150.121.781,-.Â  Meanwhile the benefit value of this product was Rp. 188.769.268 per year, obtained from 4.225 kilogram lempok and 81 kilogram crust of lempok per year.